APPLICATION OF ISOMETRIC DYNAMOMETER IN BIOMECHANICAL DIAGNOSTICS - Aceski, Aleksandar; Spasovska, Katerina; Daskalovski, Borce; Vuksanovikj, Vladimir (Faculty of physical education sport and health, Skopje, 2022)
Instruments for measuring muscle activity must meet the metric characteristics. The isometric dynamometer is an instrument that is easy to handle and can be used for both sports and clinical purposes. There are several models of dynamometers, and their choice depends on their general and technical characteristics, the purpose of testing and the budget. The most common application is the hand dynamometer, which is of great importance for monitoring the grip strength in sports where the action of the flexors in the joints of the fingers of the hand and the wrist is of primary importance, such as: judo, wrestling, gymnastics, tennis, Olympic weightlifting, rock climbing, etc.
Keywords: muscle force, instrument, muscle contraction, indicator, isometric dynamometer.